Pengembangan Flashcard Dengan Augmented Reality Android Sebagai Sarana Informasi UMKM Kota Cirebon - Ahmad Rizqi Kurniawan; Cecep Kustandi; Kunto Imbar (Universitas Negeri Jakarta, 2019)
This research aims to development Flashcard and Augmented Reality based on Android can be integrated with each other. This development aims to provide information on the diversity of Micro Small and Medium Enterprises in the Cirebon City, to Indonesian people. Researcher develop this product using Integrated Learning Design Framework learning methods. Outlines of the theories using; Development theories, Augmented Reality theories, and Micro Small and Medium Enterprises theories. First stage is analysis, second stage is development, third stage is evaluation and implementation. Result from review experts get an average score 3.6 which means very good category. From users get an average score 3.73 for one to one trials which means in very good category, and score 3.62 for small group trials which means in very good category.